Cdk-interacting protein 1 directly binds with proliferating cell nuclear antigen and inhibits DNA replication catalyzed by the DNA polymerase delta holoenzyme. - Flores-Rozas, H (1994)
Cdk-interacting protein 1 (Cip1) is a p53-regulated 21-kDa protein that inhibits several members of the cyclin-dependent kinase (CDK) family. It was initially observed in complexes containing CDK4, cyclin D, and proliferating cell nuclear antigen (PCNA). PCNA, in conjunction with activator 1, acts as a processivity factor for eukaryotic DNA polymerase (pol) delta, and these three proteins constitute the pol delta holoenzyme. In this report, we demonstrate that Cip1 can also directly inhibit DNA synthesis in vitro by binding to PCNA. Cip1 efficiently inhibits simian virus 40 replication dependent upon pol alpha, activator 1, PCNA, and pol delta, and this inhibition can be overcome by additional PCNA. Simian virus 40 DNA replication, catalyzed solely by high levels of pol alpha-primase complex, is unaffected by Cip1. Using the surface plasmon resonance technique, a direct physical interaction of PCNA and Cip1 was detected. We have observed that Cip1 efficiently inhibits synthesis of long (7.2 kb) but not short (10 nt) templates, suggesting that its association with PCNA is likely to impair the processive movement of pol delta during DNA chain elongation, as opposed to blocking assembly of the pol delta holoenzyme. The implications of the Cip1-PCNA interaction with respect to regulation of DNA synthesis, cell cycle checkpoint control, and DNA repair are discussed.